RAGAM DAN KLASIFIKASI SUMBER BELAJAR SERTA TEORI PENGGUNAAN MEDIA DALAM PEMBELAJARAN - Maftuhah, Sifroh; Syarifah, Khofifatus; Ni’mah, Mafruhatun; Anam, Saeful; Nashrullah, Nashrullah (MIDA : Jurnal Pendidikan Dasar Islam, 2026)
Abstract Effective learning depends not only on the interaction between teachers and students, but also on the selection and utilization of appropriate learning resources and media. This article aims to describe the variety and classification of learning resources and explain the theories underlying the use of media in learning. Using a descriptive-qualitative approach through literature review, this study shows that learning resources include various forms, such as messages, people, materials or programs, tools, methods, and learning environments. Learning resources are also classified into two categories, namely designed resources and utilized resources. In addition, this article outlines various theoretical foundations for the use of media including behaviorism, cognitivism, constructivism, dual coding, multimedia learning, humanism, communication theory, and Edgar Dale's cone of experience which explain how media can strengthen the learning process. The results of the study confirm that the use of media that is appropriate to the characteristics of learners and learning objectives can increase motivation, understanding, and the effectiveness of the learning process. Thus, the selection and use of appropriate learning resources and media are key to realizing more interactive, meaningful, and efficient learning. Keywords: learning resources, learning media, learning theory, educational technology, learning effectiveness.